Family Resilience of Jama'ah Tabligh: Implementation Study of the Dimensions of Legality, Household Wholeness and Gender Partnerships - Siddik, Ibnu Radwan; Pagar, Pagar; Tanjung, Dhiauddin (Universitas Islam Sultan Agung, 2022)
In recent times, family resilience discourse has become a serious concern of the government, members of parliament and observers of Islamic family law in Indonesia. The higher the rate of divorce that occurs in the community, is a form of weak and fragile family defense joints. This paper will examine the implementation of the family resilience of the Jama'ah Tabligh in Serdang Bedagai Regency in the dimensions of legality, household integrity and gender partnership. Then, this paper will also elaborate on the influence of Jama'ah Tabligh activities in the formation of family resilience among Jama'ah. This research is empirical juridical research using the approach of legal sociology and legal anthropology. Research data is analyzed using qualitative methods. Primary data sources are obtained from in-depth interview results from selected respondents using the snowball method. The results showed that the implementation of the family resilience of the Jama'ah Tabligh in Serdang Bedagai Regency in the dimensions of legality, household integrity and gender partnership was well implemented and indicated strong and resilient family resilience. This is evidenced by the high percentage of family fulfillment of respondents in the ownership of marriage certificates, child birth certificates, togetherness in the family, spousal partnerships, financial management openness and family decision-making. Jama'ah Tabligh activities greatly affect the formation of family resilience along with the stronger family members in practicing religious values both personally and together. The results of this study can be a consideration for national policy holders in realizing family resilience nationally.